Short Report: Evidence of Trepanation on a Female Individual from the Middle Bronze Age Necropolis of Casas Velhas (Melides, Portugal) - Silva, A. M. (2018)
Recent reanalysis of the human remains unearthed from the grave cists of the necropolis of Casas Velhas (Melides, Portugal) from the Southwest Iberian Middle Bronze Age, with a minimal number of 25 individuals (23 adults and 2 non-adults), allowed relevant anthropological data. This culture, although widespread in southern Portugal and nearby areas of southwest Spain in the Middle Bronze Age, is characterized by the paucity of preserved human remains and thus the anthropological knowledge of these human populations. The adult female skeleton exhumed from cist 30, the last interment of this double burial, exhibit a complete perforation on the right parietal bone. The aim of this paper is to present and discuss this defect, which most probable diagnosis is trepanation. The hole is oval shape exhibiting long term healing. A shallow remodelled area is visible around the defect, which suggests scraping method. No complications or evident reasons for the intervention were observed. In terms of mortuary practices no clear distinction was observed between this individual and others from this cemetery. The features of thistrepanation ﬁt in the majorpoints summarized by Silva(2003) for prehistoric Portuguese trepanation. Thesedata sustain theexistenceof an oldtradition of thisprocedure isthisregionof Iberia, present, at least, since the Middle Neolithic.